2012
DOI: 10.1002/bsl.2003
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Correlates of Violent and Non‐violent Hong Kong Juvenile Probationers

Abstract: There is little known about Hong Kong juvenile offenders on probation. The purpose of this study was to compare Hong Kong juvenile violent with non‐violent probationers on static demographic and psychological variables. The study comprised 109 male juvenile probationers aged 14–20 years (M = 16.97, SD = 1.44) in community transitional housing; 34 were adjudicated for violent offenses, while 75 were non‐violent. The Rosenberg Self‐Esteem Scale (RSES), Satisfaction with Life Scale (SWLS), Social Bonding Scale‐Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Effective communication among family members, a positive family atmosphere, and adequate parental monitoring and supervision are also crucial. Research has consistently demonstrated that the propensity to engage in antisocial and delinquent activities (in this case, the perpetration of traditional school bullying and cyberbullying) is likely to be reduced if the adolescents in question are healthy in terms of their psychosocial well-being (Chan & Chui, 2012, 2015a, 2015b). The failure to securely bond with their families is likely to expose adolescents to various forms of delinquency, including bullying perpetration behaviors (Chan & Chui, 2013).…”
Section: Implications Of the Findingsmentioning
confidence: 99%
“…Effective communication among family members, a positive family atmosphere, and adequate parental monitoring and supervision are also crucial. Research has consistently demonstrated that the propensity to engage in antisocial and delinquent activities (in this case, the perpetration of traditional school bullying and cyberbullying) is likely to be reduced if the adolescents in question are healthy in terms of their psychosocial well-being (Chan & Chui, 2012, 2015a, 2015b). The failure to securely bond with their families is likely to expose adolescents to various forms of delinquency, including bullying perpetration behaviors (Chan & Chui, 2013).…”
Section: Implications Of the Findingsmentioning
confidence: 99%
“…Sample items include, ‘I would like to be the kind of person my best friend is,’ ‘I talk over future plans with my parents’ and ‘I have lots of respect for the police’. The SBC has rarely been used with the Hong Kong Chinese population (see exceptions, Chan & Chui, ; Chui & Chan, , , ). In the study of Chapple et al (), the alpha coefficients of six latent social bonding constructs were between 0.46 and 0.80.…”
Section: Methodsmentioning
confidence: 99%
“…In general, juvenile probationers in Hong Kong have rarely been studied. However, in recent years, a number of studies have specifically examined their socio-psychological characteristics and their risk of recidivism (see, for example, Chan & Chui, 2012; Chui & Chan, 2011a, 2011b, 2012). In Chui and Chan's (2011a) study, juvenile probationers who were less bonded with their parents, involved in more organizational activities, and who held negative beliefs about the legal system were more likely to engage in delinquent activities, even during their probation period.…”
Section: Juvenile Probationers In Hong Kongmentioning
confidence: 99%
“…Furthermore, most of the published studies have been conducted using adult samples (see, for example, Chui, 2004, 2006), with juvenile probationers rarely being studied. Only a handful of studies set in Hong Kong, all of which have been published relatively recently, focus on this population (see, for example, Chan & Chui, 2012; Chui & Chan, 2011a, 2011b, 2012). The present study is therefore the first attempt to explore Hong Kong juvenile probationers' perceptions of their probation officers.…”
Section: Introductionmentioning
confidence: 99%